The value of csf analysis for the differential diagnosis of HTLV-I associated myelopathy and multiple sclerosis Valor da análise do LCR para o diagnóstico diferencial de mielopatia associada ao HTLV-I e esclerose múltipla - Marzia Puccioni-Sohler; Bernd Kitze; Klaus Felgenhauer; Iris T. Graef; Peter Lange; Sergio Novis; Hansotto Reiber; Beatriz Vaz (Arquivos de Neuro-Psiquiatria)
Cerebrospinal fluid (CSF) and serum of 17 patients with HAM/TSP (HTLV-I associated myelopathy/ tropical spastic paraparesis), six with multiple sclerosis and six with idiopathic epilepsy (non inflammatory control) from Brazil were analysed for the presence of intrathecal synthesis of virus-specific antibodies against measles, rubella, varicella zoster virus and herpes simplex virus by enzyme-linked immunosorbent assay (ELISA). All HAM/TSP and multiple sclerosis cases had an intrathecal immune response (oligoclonal IgG). In HAM/TSP, only 1/17 case showed a polyspecific intrathecal immune response against measles and rubella virus. In multiple sclerosis, specific antibodies against measles and rubella (MRZ response) were observed in all patients but not in the control with idiopathic epilepsy. The diagnostic and theoretical relevance of mono- and polyspecific immune responses is discussed for these chronic neurological diseases. Amostras de líquido cefalorraquidiano (LCR) e soro de 17 pacientes brasileiros com HAM/TSP, seis com esclerose múltipla e seis com epilepsia idiopática (controle não-inflamatório) foram analisadas para a presença de anticorpos para os vírus do sarampo, rubéola, varicela zoster e herpes simples pelo método de ELISA. Todos os casos de HAM/TSP e esclerose múltipla tinham resposta imune intratecal (IgG oligoclonal). Somente 1/17 casos de HAM/TSP apresentavam resposta imune poliespecifica intratecal para sarampo e rubéola. Anticorpos específicos para sarampo e rubeola (resposta MRZ) foram observados em todos os pacientes com esclerose múltipla, mas não nos controles com epilepsia idiopática. A relevância das respostas poliespecifica e monoespecifica é discutida para essas doenças neurológicas crônicas.